Acute Effects of Cadmium on the Antioxidant Enzyme Activities and Histological Structure of the Gills and Liver of Juvenile Thamnaconus septentrionalis - Xiaoran WANG; Li BIAN; Qiong HU; Bo QIN; Qing CHANG; Na YING; Yanqing WU; Liguo YANG; Siqing CHEN (Progress in Fishery Sciences, 2023)
The acute toxicity of cadmium (Cd2+) to juvenile Thamnaconus septentrionalis was determined using a hydrostatic biological assay. According to the pre-experiment results, four Cd2+ concentration gradient test groups (8.19, 9.18, 10.30, and 11.56 mg/L) and one blank control group were selected for the acute toxicity test using the equilogarithmic spacing method. The mortality, LC50, and safe concentration of Cd2+ in juvenile fish at 24 h, 48 h, 72 h, and 96 h were calculated. Based on the experimental results of acute toxicity of Cd2+ to juvenile Thamnaconus septentrionalis, the Cd2+ concentration gradients were set as 1.84 mg/L, 2.76 mg/L, 3.68 mg/L and 4.60 mg/L at the safe concentration multiple. The activities of superoxide dismutase (SOD), catalase (CAT), glutathione antioxidant enzyme (GSH-PX), and the content of malondialdehyde (MDA) in liver and gill tissues were observed at 6 h, 12 h, 24 h, 48 h, 72 h and 96 h. The results showed that as Cd2+ concentration increased, the acute toxicity gradually increased, the LC50 at 24 h, 48 h, 72 h and 96 h was 11.47 mg/L, 10.82 mg/L, 9.84 mg/L, and 9.19 mg/L, respectively, and the safe concentration of Cd2+ on juvenile filefish was 0.92 mg/L at 96 h. Within 6 h, SOD activity in each concentration group was significantly higher than that in the control group (P < 0.01); SOD activity first decreased and then increased within 6–24 h; however, from 24 h to 96 h, SOD activity of all concentration groups showed a downward trend. SOD activity in the 1.84 mg/L and 2.76 mg/L groups was always higher than that in the control group within 96 h. The enzyme activities of the 3.68 mg/L and 4.60 mg/L groups decreased to below that of the control group from 6 h to 12 h, and increased at 24 h, after which it showed a constant downward trend and remained lower than that of the control group. From 6–12 h, MDA content first decreased and then increased. At 24 h, the enzyme content in each treatment group decreased, but was still higher than that in the control group, and the difference was significant (P < 0.05). From 12 h to 48 h, the 1.84 mg/L and 2.76 mg/L groups showed a trend of first decreasing and then increasing, whereas within the 24 h to 96 h period, the MDA content in the 3.68 mg/L and 4.60 mg/L groups kept increasing, and was significantly higher than in the control group (P < 0.01). At 6 h, CAT activity in all treatment groups was significantly increased when compared to that of the control group; however, CAT activity in the 3.68 mg/L and 4.60 mg/L groups was significantly inhibited at 48–96 h. Overall, the activity of GSH-PX in each treatment group showed a decreasing, increasing, and then decreasing trend within 6–96 h. The activity of GSH-PX in the 1.84 mg/L group was higher than that in the control group within 96 h. When compared with the control group, the activity of the 2.76 mg/L and 3.68 mg/L groups decreased from 24 h to 96 h, and the longer the stress time, the lower the activity. In the highest concentration group (4.60 mg/L), the enzyme activity first increased and then decreased, and the GSH-PX activity decreased to 300.12 U/mg prot at 96 h, which was significantly different from that in the control group (P < 0.01). In the 1.84 mg/L group, there was no significant change in liver tissue within 72 h, but in the 1.84 mg/L group at 96 h and the 2.76 mg/L group at 24 h, the cell volume was slightly increased, cells had an irregular shape, and some cell membrane boundaries were blurred. At 48–96 h in the 2.76 mg/L group, and 24–48 h in the 3.68 mg/L and 4.60 mg/L groups, the liver cells were disordered and scattered, and the structure of liver cells was mostly incomplete. After 72–96 h in the 3.68 mg/L group and 72 h in the 4.60 mg/L group, the abnormality of liver cells was significantly aggravated, including cell hypertrophy, large area disintegration, cytoplasm overflow, and cell cavitation. At 96 h in the 4.60 mg/L group, the nucleus shrank, intracellular material gathered, and a large irregular blank appeared. For 72 h in the 1.84 mg/L group and 24 h in the 2.76 mg/L group, there was no significant change in gill tissue structure, whereas after 96 h in the 1.84 mg/L group, 48 h in the 2.76 mg/L group, and 24 h in the 4.60 mg/L group, the gill microplates were curved and club-like with mucus secreted around them, and the epithelial cells were enlarged, showed edema and partial hyperplasia, and the distance between the adjacent lamella became smaller. At 72 h in the 2.76 mg/L group, and at 24–48 h in the 3.68 mg/L and 4.60 mg/L groups, a small number of adjacent gill lamellae would fuse and form a small epithelial cell plate, with a large amount of mucus around them, and the length of gill lamellae was significantly shortened. In the 2.76 mg/L group at 96 h and the 3.68 mg/L group at 72 h, most of the basal lamellae had fused together, the epithelial cells of the gill lamellae were swollen and showed hyperplasia, and exfoliated epithelial cells were scattered around. At 96 h in the 3.68 mg/L group and 72–96 h in the 4.60 mg/L group, adjacent gill lamellae had adhered and fused with each other without a free end, and a large number of cells were necrotic and exfoliated.